Unlocking the Performance of Female Managers in a Global Cosmetics Company through the Lens of Gender at Work Framework - Widiati, Restu; Siscawati, Mia; Costantini, Arianna; Soetjipto, Budi W (Program Studi S3 Ilmu Manajemen, 2024)
Despite the growth and dynamism within the cosmetics industry, gender disparities in senior leadership persist, raising critical questions about how an ecosystem and various forces can impact the performance and professional advancement of female leaders. This qualitative case study explores the dynamics of female managerial performance within a global cosmetics company, focusing on two subsidiaries in countries with lower gender equality indices, namely India and Indonesia. Using the modified Gender at Work Framework developed by Rao et al. (2016), the research analysed the multifaceted factors influencing the performance of female managers within this industry. By navigating the intertwined areas of company policies, resources, organisation norms, and self-consciousness, the study aims to unearth nuanced insights into female managers' challenges and opportunities in these settings. Four themes are emerging: (1) Gender Equality at work, (2) Ownership of Performance and Career, (3) Digital Capability and innovation, and (4) Support system. Other findings of this study concern the various parties and the different environments that may foster the performance of female managers. This research contributes to the broader context of gender in the workplace, shedding light on strategies to enhance the performance and advancement of female managers within the cosmetics industry, particularly in regions where gender disparities persist.